Technology use in speech and language therapy: digital participation succeeds through acceptance and use of technology - Leinweber, Juliane; Alber, Birte; Barthel, Maria; Whillier, Alexander Sean; Wittmar, Silke; Borgetto, Bernhard; Starke, Anja (Frontiers in Communication, 2023)
Introduction In Germany, as around the world, the use of digital media in speech and language therapy became part of the service during the COVID-19 pandemic. This resulted in a need for empirical studies on the use and acceptance of digital media technologies, to determine users' requirements and concerns regarding the newly mandated technologies, in order to support its expansion in education and training going forward. “Acceptance” has been previously identified as an important aspect behind successful technology adoption. Therefore, two online questionnaire studies were conducted to explore how technology use is accepted among speech and language therapists in Germany. Methods Study 1 involved a questionnaire about video therapy with 15 question groupings, examining technology acceptance and competence. From 841 initial respondents, 707 complete responses were included in the analysis. Study 2 involved a different questionnaire, examining technology acceptance and digital media in therapy. In total, 79 individuals participated in the second survey. Study 1 data were analyzed to identify unifying factors underlying respondent attitudes and was followed up with a logistical regression; Study 2 data were analyzed with multiple linear regression. Results In Study 1, external inhibiting and facilitating conditions were identified which had an impact on attitudes toward video therapy adoption and its intended future use. In Study 2, the modified model of the Unified Theory of Acceptance and Use of Technology (UTAUT) explained 58.8% of the variability in therapist's Behavioral Intention to Use digital media. Here, Performance Expectancy was a significant predictor. Conclusions Both studies investigated facilitating and inhibiting factors for the implementation of digital media including video therapy in future speech therapy services. Results demonstrated that the use is accepted in therapy. Therefore, optimal conditions—both institutional and individual—are needed to enable digital participation for therapists and patients. In future education and training, trainers should focus on the functional aspects of the technologies to be used, in order to positively influence Performance Expectancy in a targeted manner and thus increase the therapists' intention to use digital technology in therapy, which in turn promotes patients' digital participation.